Development of a microfluidic platform for high‐throughput screening of non‐viral gene delivery vectors. Issue 3 (19th December 2017) - Giupponi, Elisa; Visone, Roberta; Occhetta, Paola; Colombo, Federica; Rasponi, Marco; Candiani, Gabriele
Abstract: The grail of gene delivery is the development of delivery vectors as effective and non‐cytotoxic as possible. In this regard, there is an urgent need of new tools for the straightforward and quantitative assessment of transfection efficiency and cytotoxicity simultaneously. We herein reported the development and validation of an easy‐to‐use lab‐on‐chip platform to perform cell transfection assays for unbiased, high‐throughput selection of more and more effective gene delivery vectors by using two commercially sourced lipids, Lipofectamine 2000 ® and FuGene ® 6. A single PDMS‐layer platform was endowed with: i) a chaotic serial dilution generator, designed for the automatic generation of a linear lipoplex dilution (from 100% to 0% with 25% steps) independently delivered to; and ii) the downstream culture and transfection module consisting in five units, each composed of 33 serially connected and fluidically connected culture chambers for trapping small populations of ≈10 cells/chamber. In the absence of any transfectant, cells spread and duplicated up to 2 days. Besides, cells were transfected with EGFP‐encoding reporter gene. The very facile visual inspection of the microdevice by means of a microscope and a semi‐automated analytical method allowed pinpointing the best transfection conditions in terms of efficiency, cytotoxicity, cell doubling rates, and morphological changes at once. Abstract : The authors developed and presented a microfluidic platform intended for cell trapping, culture and gene delivery. The device consists in a serial dilution generator, designed for the simultaneous administration of a controlled dilution of lipoplexes (from 100% to 0% with 25% steps) upstream to a culture and transfection area composed by five units, with 33 serially‐connected chambers each. The microdevice enabled to evaluate best transfection conditions, in terms of efficiency, cytotoxicity and cell doubling rates at once.